2020
DOI: 10.3389/fpls.2020.00093
|View full text |Cite
|
Sign up to set email alerts
|

O3-Induced Priming Defense Associated With the Abscisic Acid Signaling Pathway Enhances Plant Resistance to Bemisia tabaci

Abstract: Elevated ozone (O 3) modulates phytohormone signals, which subsequently alters the interaction between plants and herbivorous insects. It has been reported that elevated O 3 activates the plant abscisic acid (ABA) signaling pathway, but its cascading effect on the performance of herbivorous insects remains unclear. Here, we used the ABA-deficient tomato mutant notabilis (not) and its wild type, Ailsa Craig (AC), to determine the role of ABA signaling in mediating the effects of elevated O 3 on Bemisia tabaci i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 62 publications
(72 reference statements)
1
10
0
Order By: Relevance
“…This may be due to the signal transduction of plant hormones, rather than plant hormone biosynthesis, in response to GB. Furthermore, recent studies have revealed that ABA has an important role in resistance to plant disease (Cao et al ., 2019; Guo et al ., 2020). Mang et al .…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the signal transduction of plant hormones, rather than plant hormone biosynthesis, in response to GB. Furthermore, recent studies have revealed that ABA has an important role in resistance to plant disease (Cao et al ., 2019; Guo et al ., 2020). Mang et al .…”
Section: Discussionmentioning
confidence: 99%
“…ABA is well known for its involvement in response to abiotic stress, and its functions in defense response have been also illustrated (García-Andrade et al 2020;Guo et al 2020b). In this study, 16 ABA-related genes were identi ed among the core genes (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Grain number per panicle1 ( GNP1 ), which encodes gibberellin biosynthesis gene GA20ox1 , affects seed per panicle in rice ( Wu et al., 2016 ). To unfold GNP1 effect on sink, source, and flow in regulating grain yield in rice, Zhai et al. (2020) compared ‘Lemont’, a japonica cultivar, with its near isogenic line (NIL-GNP1 TQ ) in ‘Lemont’ background, containing an allele at GNP1 locus from a high-yielding indica cultivar ‘Teqing’.…”
Section: Genetic and Molecular Basis Of Tradeoff To Developing Breeding Populations And Cultivarsmentioning
confidence: 99%
“…Significantly lower carbohydrate accumulation in culms and leaf sheath before heading in comparison to ‘Lemont’ contributed to low seed setting rate and grain weight of IS in NIL-GNP1 TQ . However, significantly increased grain number panicle −1 from introgression of GNP1 TQ into ‘Lemont’ did not result in significant improvement in grain yield of NIL-GNP1 TO primarily due to significant low sink activities in IS and insufficient source supply, not sufficient to meet the increased sink capacity demand ( Zhai et al., 2020 ).…”
Section: Genetic and Molecular Basis Of Tradeoff To Developing Breeding Populations And Cultivarsmentioning
confidence: 99%
See 1 more Smart Citation